FINANCIAL INNOVATION, RISK MANAGEMENT, AND BANK PERFORMANCE - Zouari, Ghazi; Abdelmalek, Imen (Copernican Journal of Finance & Accounting, 2020)
Several researches conducted from the angle of corporate governance reveals that the majority of the work that examines the direct association between financial innovation and bank performance has displayed mixed results and has ignored the indirect relationship between these two variables through the risk management of incurred by the bank. In this context, the purpose of this study is to investigate whether or not there is a mediating effect of risk management on the relationship between financial innovation and bank performance. Data collected from annual activity reports of banks listed on the Tunis Stock Exchange is analyzed, and used to validate the theoretical and empirical contributions of our article. The empirical study uses the Panel data extracted from 10 banks, over the period ranging from 2009 to 2017, and the Baron and Kenny (1986) mediation approach has been estimated, using specifications of random effects. Our empirical analysis substantiates that financial innovation has a positive direct effect on stock market performance, and a non-significative impact on financial profitability. Additionally, our results show that improving the stock market performance of banks by financial innovation depends on the mediator role of the operational risk management. To remain improving performance, Tunisian banks must pay more attention on special training of bank managers whose function relate to the choice of financial innovations and manage the associated risks.